ASSESSING KNOWLEDGE AND PRACTICE AMONG PATIENTS WITH DAIBETES AT TERTIARY CARE HOSPITAL - Tahir, Muhammad; Adil, Muhammad; Khalid, Shahid Raza; Swati, Nazish Khan (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess knowledge and practice among patients with type 2 diabetes and to study their demographic details.Study Design: Cross-sectional observational study.Place and Duration of Study: Outpatient department, Combined Military Hospital Abbottabad, from Oct 2016 to Mar 2017.Material and Methods: A total of 430 patients with type 2 diabetes who attended outpatient department for routine visits were included in the study after taking consent. While patients with type 1 DM, chronic illnesses like; cardiac failure, renal failure and psychiatric illness were excluded from study. All patients were selected by non probability convenient sampling technique. Data was collected by using a questionnaire and was analyzed by using SPSS software. Descriptive statistics were produced.Results: Out of 430, 232 (53.95%) were male while 198 (46.04%) were female with male to female ratio of 1.17:1. The greatest numbers of patients were in age group 60-69 years with average duration of DM 1-5 years in about 35.35%. Seventy seven percent of patients had positive family history of disease. About 40% of patients had average knowledge with mean score of 2.02 while 52.5% had satisfactory practice and routine follow up. Eye complications, neuropathy and nephropathy were major complications observed.Conclusion: The overall level of knowledge and practice concerning diabetes is average. This highlights the importance of awareness campaign and patient counseling to improve their knowledge regarding diabetes. There should be continuous process of evaluation to improve patient care and also health care delivery system.